Risk factors for autism in Baghdad city - Tawfeeq, Wafa Faiq; Mukhaiser, Maha Hussein; Al-Hemiary, Nesif Jasim (AL-Kindy College Medical Journal, 2016)
Background: Autism is a complex developmental disability that typically appears during the first three years of life. Autism affects the normal development of the brain in the areas of social interaction and communication skills.Objectives: To identify risk factors for Autism among a sample of autistic children in Baghdad city. Type of the study: this is a case – control, study. Methods: This study was conducted during the period of data collection extended from first of November 2010 until the first of April 2011,The total number of children involved was 100children with diagnosis of autism. Handred children who are free from autism were taken as the control sample. Results: there was a significant association between paternal age and the risk for autism, fathers older than 40 years had 11 times increased risk of having an offspring with autism, (p=0.043).Psychologicalproblems, showed a statistically increased risk of autism associated with maternal history of (maternal unhappy emotional state), the odds ratio of this risk factor was seven (p=0.01). Post term (14% in cases vs. 2% in controls) (P=0.005, OR 8.80) and neonatal jaundice (30% in cases and 11% in controls) (P=0.001, OR 3.71) were significantly associated with autism.Bottle-feeding showed the highest significant associations with risk of autism (p=0.004, OR=2.84).Conclusion:Autism has many associated risk factorslikepaternalage (fathers older than 40 years),psychological problems (maternal unhappy emotional state),post term,neonataljaundiceandbottle-feeding